ESTABLISHMENT AND TREATMENT OF MURINE COLONOIDS TO STUDY THE EPITHELIAL EFFECTS OF INTESTINAL INFLAMMATION IN VITRO. (26th January 2023) - Crawford, Erin; Mentrup, Heather; Novak, Elizabeth; Mollen, Kevin
Abstract: BACKGROUND: Disruption of the intestinal epithelial barrier is a hallmark of inflammatory bowel disease (IBD). The 3-dimensional colonoid culture system is a useful in vitro model to study intestinal stem cell dynamics and epithelial cell physiology in IBD pathogenesis. However, we have shown that in vivo epithelial changes are not necessarily retained in colonoids established from mice undergoing acute inflammation using a DSS model and primarily reflect stem cell physiology rather than that of terminally differentiated cells. We developed experimental methods to address this limitation. We terminally differentiate colonoids or create 2-D monolayers, and challenge them with a cocktail of inflammatory mediators that are typically elevated during IBD. METHODS: Murine colonoids are established by isolating colonic crypts and plating them in basement membrane matrix. Over 3 to 5 days, crypt structures develop into spheroid colonoids 250 μm in diameter, forming a prominent lumen surrounded by a thin layer of epithelial stem cells. They are passaged a minimum of two times and then are either 1) terminally differentiated by incubating the colonoids with Differentiating Media or 2) used to establish intestinal epithelial monolayers. Inflammation is then induced by incubating cells with a cocktail of inflammatory mediators (TNFa, IL-1b, IFNg, H2 O2 ). Protein is collected after 72 hours, and expression of proteins involved in mitochondrial biogenesis were assessed (n=3). RESULTS: We found that changes in mitochondrial dynamics, reflective of key metabolic changes in the epithelium that are observed in colonic scrapings of DSS-treated mice are not recapitulated in traditional colonoids derived from mice on the same DSS regimen. We found that changes in expression and protein levels of peroxisome proliferator-activator receptor-gamma coactivator-1a (PGC1a), the master regulator protein of mitochondrial biogenesis, were not maintained in colonoids. After terminally differentiating colonoids and subsequently inducing inflammation, we were able to recapitulate a failure of mitochondrial biogenesis failure that is a hallmark of both human IBD and murine colitis. Protein expression of PGC1a as well as downstream transcription factor A, mitochondria (TFAM) were both decreased when assessed via western blot. DISCUSSION: Colonoids are a useful tool for studying colonic physiology in vitro, however are limited in their ability to evaluate the effects of in vivo inflammation on the mitochondrial function and cellular metabolism. When removed from the intestinal milieu, crypt cells demonstrate a recovery of mitochondrial health and reflect stem primarily stem cell physiology. Our strategies provide opportunities for organoid manipulation which, when employed properly, can shed light on key aspects of intestinal epithelial mitochondrial function during inflammation.